Atomic-scale intercalation and defect engineering for enhanced magnetism and optoelectronic properties in atomically thin GeS - Anthony C. Iloanya; Srihari M. Kastuar; Gour Jana; Chinedu E. Ekuma (Scientific Reports)
Abstract We investigate the synergistic effects of chromocene intercalation (GeS–Cr $$(C_5H_5)_2$$ ) and randomly distributed sulfur vacancies on the optoelectronic properties of atomically thin GeS using advanced first-principles many-body simulations. We demonstrate the emergence of a magnetic ground state in GeS, driven by weak chemical interactions between the GeS host and the intercalated organometallic chromocene. Using large-scale, first-principles many-body simulations that account for randomly distributed sulfur vacancies and the dielectric screening within the hybrid material, we show the tunability of the optoelectronic features. Specifically, we observe enhanced absorption in the range of $$\sim$$ 0.21 to 3.5 eV, including absorption below the bandgap threshold as the vacancy concentration is tuned between 1 and 5%. The emergent Lifshitz tails are in excellent agreement with our numerical calculations. The predicted features and tunability underscore the potential of defect engineering for applications in magneto-optics and high-density data storage, where precise manipulation of light with magnetic fields is crucial for advanced applications.